Dari Al-Ghazali ke Ibnu Khaldun: Dialektika Konservatisme, Rasionalisme, dan Pragmstisme dalam Filsafat Pendidikan Islam - Basori Basori; Izzatul’Aisy Izzatul’Aisy; Ade Zelda Savitri Siregar; Daimatussalimah Daimatussalimah (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2025)
This article explores the dynamics of Islamic educational thought through the perspective of three influential figures: Al-Ghazali, Ikhwan al-Shafa, and Ibn Khaldun. Al-Ghazali, representing the conservative school, emphasizes education as a process of character building and drawing closer to Allah. Ikhwan al-Shafa, with their rational-religious school, emphasizes the importance of logic, observation, and dialectics in acquiring knowledge. Ibn Khaldun, as a representative of the pragmatic school, emphasizes education that is oriented towards social contribution and based on reality. This article analyzes the fundamental differences and contemporary relevance of these three schools, showing that an ideal Islamic education is one that can unite the three schools within the framework of an adaptive and responsive curriculum.